Rekontruksi Kesadaran Hukum dan Keadilan Sosial : Integrasi Hukum Ekonomi, Digital, Perdata, Pidana, dan Tata Negara melalui Hak Kewarganegaraan dan Islamic Sociological Jurisprudence Theory - Nova Fitriana Kusumaningtyas; Ahmad Muhammad Mustain Nasoha; Inasa Areeva; Alifia Arin Nabila; Zulfa Maulida (Majelis: Jurnal Hukum Indonesia, 2026)
This article aims to reconstruct legal awareness and social justice in the context of a contemporary rule of law through the integration of economic law, digital law, civil law, criminal law, and constitutional law within the framework of citizenship rights and Islamic Sociological Jurisprudence Theory. The main problem of this research stems from the fact that the development of the modern legal system tends to be sectoral, formalistic, and not fully responsive to social change, unequal access to justice, and digital transformation that affects the relationship between citizens and the law. This research uses a normative legal research method with a conceptual, legislative, and sociological approach. The results of the study indicate that legal awareness is not simply understood as formal compliance with norms, but must be developed as a substantive awareness oriented towards social justice, protection of citizenship rights, and public welfare. From the perspective of Islamic Sociological Jurisprudence, law is positioned not only as a regulatory instrument, but also as a means of social transformation based on the values ​​of justice, moral responsibility, and siding with the interests of society. Integration across legal branches is crucial for the legal system to more comprehensively address issues related to economics, digitalization, civil relations, criminal enforcement, and state governance. Therefore, the reconstruction of legal awareness must be directed toward establishing a legal paradigm that is integrative, humanistic, adaptive, and socially just.